Rejuvenating old, senile orchards of tropical and subtropical fruits for enhanced production and improved quality: A review - KUMAR, RAJESH (The Indian Journal of Agricultural Sciences, 2015)
Fruit production addressing the challenges of nutritional and livelihood securities, needs strategic planning and proper interventions for higher productivity and improved quality. In this context harnessing full production potential of perennial fruit crops, is necessary for ensuring sustainability and competitiveness of the industry and profitability to the growers. Majority of the perennial fruit crop orchards across vast tract of the country are characterized by the prevalence of old and unproductive trees with reduced fruiting potential (30-35%). The prolonged neglect in their management practices virtually make them unproductive. Replacing the old orchards through a new plantation is a more demanding process. Rejuvenation technology encompassing reiterative pruning, top-working and canopy rebuilding for augmenting productivity could be a viable option to be exploited for restoring health and vigour of the trees to ensure profitability of the orchards. Rejuvenation techniques confers multiple benefits such as early transformation and quality production from old unproductive, senile trees by better sunlight interception, utilization and efficient use of open space and applied inputs. The productivity augmentation is found to the tune of 2 - 6 times in various fruit crops through this technology has been demonstrated successfully in the recent past. Besides reiterative pruning, cultural operations like nutrition, irrigation, intercropping, mulching and plant protection measures need to be carried out properly and carefully to help improving soil health, tree vigour and production efficiency. However, faster adoption of this technology warrants that some physiological apprehensions of the growers that the old perennial trees will die after heavy pruning and they require abnormally long time to rebuild their canopy and bear profitability need to be removed through large scale field demonstrations. The technology is economically viable and can bring noticeable change in productivity of declining old orchards. Further research on physiology of shoot growth and bearing of severly pruned trees will not only help refinement of actual pruning process but also the associated cultural practices that are essentially required to expedite the whole re-invigorating process.